Islam : a mosaic, not a monolith - Gregorian, Vartan (Washington, D.C. : Brookings Institution Press, 2003)
For readers unfamiliar with the world's fastest-growing religion, Gregorian provides an accessible overview of its tenets, institutions, evolution, and historical role, along with insights into the current state of Muslim societies and the challenges they face.
A brief survey of Islam -- Clash of modernists and traditionalists -- Challenges of the twentieth century -- Islamism : liberation politics -- Quests for democracy and modernity -- Need for mutual knowledge and understanding.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Islamic countries -- Politics and government -- 20th century; Islam and politics -- Islamic countries; Islamic renewal -- Islamic countries; Nationalism -- Islamic countries -- History -- 20th century; Islam and politics; Islam et politique -- Pays musulmans; Islamisme; Renouveau islamique -- Pays musulmans; Nationalisme -- Pays musulmans -- Histoire -- 20e siècle.; Pays musulmans -- Politique et gouvernement -- 20e siècle.; POLITICAL SCIENCE -- Political Process -- General; RELIGION -- Islam -- General; Islam and politics; Islamic renewal; Nationalism; Politics and government; Islamic countries; Islam; Islam; Stromingen (cultuur); 1900-1999; History